Класифікація форм оцінювання ефективності діяльності органів та установ виконання покарань - Круглова, А. Є.; Kruglova, A. Y. (Право і безпека. - 2016. - № 1 (60). - С. 50-54, 2016)
Здійснено класифікацію форм оцінювання ефективності діяльності органів та установ виконання покарань за певними критеріями: об’єктом, часом, періодичністю, суб’єктним складом, формою проведення та ін., надано їх коротку характеристику, а також запропоновано на рівні окремого закону України «Про оцінювання ефективності діяльності органів та установ виконання покарань» закріпити форми проведення оцінювання, правовий механізм їх утілення, порядок і періодичність їх застосування.

The article’s objective is the implementation of the classification of the forms of evaluating the effectiveness of the activities of penal agencies and institutions on various criteria, because it is necessary for a more detailed and in-depth study of the effectiveness of penal agencies and institutions at certain stages of management, their specific actions, methods of achieving the objectives, etc. The relevance of this theme is that the efficiency of any state authority is always a priority research for both scholars and practitioners. One of the most effective mechanisms to determine, along with the further improvement of the work of the state authorities in the country is the evaluation of their work, the study of some aspects of their work that in some way affect their performance. Now the problem of evaluating the effectiveness of the activities of penal agencies and institutions is quite urgent. This is due to the need to respect the demands of international and legal acts by Ukraine concerning the proper treatment of the detainees, respect for their dignity, despite the crimes committed by them. Using specific forms of evaluating the activities of penal agencies and institutions and their officials it is possible to realize the real adherence to and implementation of the above principles, their effective implementation into national legislation. The author of this article has accomplished the classification of the forms of evaluating the effectiveness of the activities of penal agencies and institutions according to certain criteria, object, time, frequency, subjective composition, form of conduction, etc.; the author has provided their brief characteristics, as well as stated the need to consolidate the forms of conducting evaluation, legal mechanism for their implementation, procedure and frequency of their use on the level of a separate Law of Ukraine «On Evaluating the Effectiveness of the Activities of Penal Agencies and Institutions».

Осуществлена классификация форм оценки эффективности деятельности органов и учреждений исполнения наказаний по определённым критериям: по объекту, времени, периодичности, субъектному составу, форме проведения и т. п., предоставлено их краткую характеристику, а также предложено на уровне отдельного закона Украины «Об оценке эффективности деятельности органов и учреждений исполнения наказаний» закрепить формы проведения оценки, правовой механизм их реализации, порядок и периодичность их применения.
Classification of the forms evaluating the effectiveness of the activities of penal agencies and institutions
Классификация форм оценивания эффективности деятельности органов и учреждений исполнения наказаний
Круглова, А. Є. Класифікація форм оцінювання ефективності діяльності органів та установ виконання покарань /А. Є. Круглова // Право і безпека. - 2016. - № 1 (60). - С. 50-54.
Kruhlova, A.Y. (2016), “Classification of the forms evaluating the effectiveness of the activities of penal agencies and institutions” [“Klasyfikatsiia form otsiniuvannia efektyvnosti diialnosti orhaniv ta ustanov vykonannia pokaran”], Pravo i Bezpeka, No. 1, pp. 50–54.
Keywords: Кримінально-виконавче право. Criminal and Executive Law. Уголовно-исполнительное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; оцінювання ефективністі; ефективність; установи виконання покарань; нормативно-правовий акт; evaluation; efficiency; penal institution; legal act; оценивание эффективности; эффективность; учреждения исполнения наказаний; нормативно-правовой акт